Program DESA ASRI: Penguatan Ketahanan Pangan dan Pengelolaan Sampah di Desa Purwodadi, Nagan Raya: indonesia - Kusumawardani, Eva Flourentina; Aristanjaya, Reza; Aboni, Andes; Panjaitan, Risky Amalia; Armi, Luna; Auliya, Rahmah; Hajjar, Siti Fhadilla; Moniza, Moniza; Naben, Maria Della Imersi; Ramazan, Feri; Wibawa AB, Sultan Khana; Sasdiyanti, Shapna; Lestari, Rachmatika; Siregar, Mawaddah Putri Arisma (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
The concept of Desa Aman, Sehat, dan Rindang (Desa ASRI), or Safe, Healthy, and Green Village, is an initiative aimed at creating a prosperous and sustainable village environment by prioritizing health, security, and environmental conservation. This program, initiated by the TIM PPK ORMAWA HIMAKESMAS FKM UTU in Purwodadi Village, includes various activities designed to enhance the quality of life for the community. One of the key components is the Waste Bank, which not only serves as a waste management facility but also supports the Sustainable Development Goals (SDGs) by encouraging residents to sort and recycle organic and inorganic waste. Additionally, the production of eco-enzymes, derived from the fermentation of organic materials, provides an environmentally friendly cleaning solution that helps reduce pollution. The vertiminaponic program, which combines fish farming with vegetable cultivation in household gardens, plays a crucial role in supporting local food security and economic resilience. These initiatives are further reinforced by the village qanun, a local regulation that ensures each program is implemented effectively and sustainably. Through collaboration and active community participation, Desa ASRI aims to create a safe, healthy, and green environment that benefits local residents while also attracting tourists and promoting broader environmental awareness.